KIF13A mediates influenza a virus ribonucleoproteins trafficking - Ramos-Nascimento, Ana (2018)
The deposited article version contains attached the supplementary materials within the pdf. This publication hasn't any creative commons license associated. The deposited article version is a "JCS Advance Online Article" provided by The Company of Biologists, and it is the "Accepted manuscript" posted online on 23 October 2017.